Private higher education in Ethiopia: risks, stakes and stocks. Issue 3 (3rd March 2020) - Tamrat, Wondwosen; Teferra, Damtew
ABSTRACT: Private higher education institutions operate amidst a litany of risks that can affect their operations and threaten their existence. This study was conducted to identify and analyze the nature and types of risks faced by Ethiopian private higher education institutions through the perspectives of their own academics. The findings revealed that the major types of risks faced by private higher education institutions relate to the broader areas of policy and regulation, financing, teaching and learning, infrastructure and resources, and research and outreach. Among others, the specific types of risks identified were found to be driven by the nature of institutional establishment and operations, resources available, and policies and regulations governing the private higher education sector. The study further established that, in addition to their contribution towards the strategic management of the sector, understanding the pattern and trends of risks is paramount to ensuring the survival—and advancement—of the fledgling private higher education sector in Ethiopia.